1998
DOI: 10.1080/01621459.1998.10473790
|View full text |Cite
|
Sign up to set email alerts
|

Approximately Exact Inference for the Common Odds Ratio in Several 2 × 2 Tables

Abstract: The conditional maximum likelihood estimator (MLE) of the common odds ratio in a sequence of independent 2 x 2 tables is known to be superior to the Mantel-Haenszel estimator in terms of asymptotic efficiency and has the further advantage that its exact distribution is known. However, a long-standing barrier to the widespread use of this estimator has been computational intractability; in particular, the calculation of significance levels, confidence sets, and power based on the exact distribution requires fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…Hwang and Yang [HY01] presented an optimality theory for mid-P-values in 2×2 contingency tables, showing how this P-value is the expected value of an optimal P-value resulting from a decision-theoretic approach. Strawderman and Wells [SW98] showed that ordinary P-values obtained with higher-order asymptotic methods without continuity corrections for discreteness yield performance similar to that of the mid-P-value.…”
Section: The Mid-p-value For Significance Testsmentioning
confidence: 96%
“…Hwang and Yang [HY01] presented an optimality theory for mid-P-values in 2×2 contingency tables, showing how this P-value is the expected value of an optimal P-value resulting from a decision-theoretic approach. Strawderman and Wells [SW98] showed that ordinary P-values obtained with higher-order asymptotic methods without continuity corrections for discreteness yield performance similar to that of the mid-P-value.…”
Section: The Mid-p-value For Significance Testsmentioning
confidence: 96%
“…One important feature of this work is that all the investigated methods are used without continuity correction; ordinary p-values calculated in this fashion can be viewed as an approximation to the mid-P value; see Pierce and Peters (1999) and Davison and Wang (2002). The difference between comparing an exact approach with a continuity corrected approximation, and comparing the mid-P approach with the approximation is mentioned also in Strawderman and Wells (1998) for the case of several 2 × 2 tables. In general this view entails a trade-off between the control over the Type I error rate and the decrease in the conservativeness of the corresponding confidence intervals.…”
Section: Introductionmentioning
confidence: 98%
“…Also, highly accurate saddlepoint approximations have been applied with success (Strawderman and Wells 1998).…”
Section: The Softwarementioning
confidence: 99%